Assessment Models for Evaluating the Combined use of Agile, User-Centered Design and Lean Startup in the Context of Software Development: A Grey Literature Review - Machado, Michele; Salerno, Larissa; Marczak, Sabrina; Bastos, Ricardo (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2020: Anais do XIX Simpósio Brasileiro de Qualidade de Software, 2020)
In an attempt to reduce the risk accompanied by innovation, IT companies have invested in fostering agile development practices in combination with Lean Startup and User-Centered Design. Going through this transformation in large companies can be a challenging endeavour without an instrument to help the teams to assess how they are evolving towards the new approach. This paper reports on a grey literature review that aimed to identify which instruments, if any, are used by industry professionals and how they use them. Unfortunately, we could not find any grey literature; thus we moved to seek to identify whether assessment models were available for a combined use of the approached two-by-two (e.g., agile and UCD), or even individually. We report on the 11 identified materials, which report on the existance of 7 distinct models. We learned that the Spotify Squad Health Check is the most cited model; that all models consider quality indicators; that they adopt distinct strategies to appluy the models such as workshops or online tools; and that the results yield by the models application is often recorded in whiteboards or online tools in the form of a backlog of improvements or of quality indicators. Our grey literature review results suggest that the topic is still maturing even among industry professionals and there is room for research in the topic.